PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP HASIL BELAJAR SISWA KELAS IV SD PADA MATA PELAJARAN IPA - Andi Dewi Riang Tati; Syamsuryani Eka Putri Atjo; Asdil Ashar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2022)
This study aims to determine the description of the Talking Stick learning model in fourth grade elementary school students, how the description of student learning outcomes in science subjects, and how the influence of the Talking Stick learning model on student learning outcomes in science subjects in grade IV SDN 339 Lagosi, Pammana District, Wajo Regency. . The population in this study were fourth grade students at SDN 339 Lagosi, Pammana District, Wajo Regency. This study uses a Quasi Experimental Design. Data collection techniques used through observation, tests and documentation. The data that has been collected by the researcher is then analyzed through descriptive statistical analysis techniques and inferential statistics. Based on the research data, after being analyzed, it showed that the criteria of students before being given treatment indicated the criteria needed for guidance, while after being treated, they showed sufficient criteria. As for the inferential statistical analysis, it shows that there is an effect of the Talking stick learning model on student learning outcomes in the fourth grade science subjects at SDN 339 Lagosi, Pammana District, Wajo Regency, with H0 rejected and Hα accepted. So it can be concluded that the description of the Talking Stick learning model in science subjects for class IV SDN 339 Lagosi, Pammana District, Wajo Regency can be used and is in the good category, and there is an influence on student learning outcomes after being given treatment in the form of Talking Stick learning model on student learning outcomes. in the fourth grade science subject at SDN 339 Lagosi, Pammana District, Wajo Regency.